Hubungan Asupan Zat Besi (Fe) Dan Status Gizi Dengan Prestasi Belajar Siswa Sekolah Dasar Di SD Negeri Kudu 02 Kecamatan Baki Kabupaten Sukoharjo - DESIAWAN, Arga, Elida Soviana, S.Gz., M.Gizi, Dr. Listiana Dharmawati S., M.Si (2015)
Introduction: Learning achievement is very affected by infection, food intake, and nutrient status. The lack of iron and the insufficient of iron need within the body will cause the event of iron deficiency anemia. The low of child nutrient status will lead to negative impact on his learning achievement. Objective: This research is to unveil the relationship between iron (Fe) and nutrient status with elementary school students' learning achievement of Kudu 02 Baki public elementary school district regency of Sukoharjo. Research Method: Type of research used in this research is observational with cross-sectional approach. The samples used are III, IV and V grade students which amount to 46 students. The sampling technique used is totalize population. Iron (Fe) intake is acquired by using recall technique 3 x 24 hours not consecutively while the nutrient status is acquired by using anthropometry measurement and for the learning achievement is obtained using the last UAS grades followed by students including natural science, math, and Bahasa courses. Result: This research shows that mostly student with iron intake is less than 39 students (84%). The most of nutrient status is on normal category which amounted to 26 students (56%). The most of learning achievement is in on normal category which is 23 students (50%). Conclusion: There is no relationship between iron (Fe) intake and nutrient status with elementary school students' learning achievement of Kudu 02 Baki public elementary school district regency of Sukoharjo.